Retrospective evaluation and descriptive analysis of the prevalence of anatomical structures and variations in CBCT images before dental implant planning in a group Turkish population, part I - Allaberdiyev, Merdan; Avsever, Ismail Hakan; Akyol, Mesut; Ayran, Şükran; Peker Öztürk, Hilal; Ozarslanturk, Savaş (Springer-Verlag Italia s.r.l., 2024)
Purpose: The aim of this study is to emphasize the importance of using cone-beam computed-tomography in order to determine the anatomical structures and their variations before the treatment in patients who apply to the dentist clinic for implant treatment. Methods: In the study, CBCT images of 500 adult patients (240 female and 260 male), aged between 21 and 82 years, who applied for implant treatment due to missing teeth, were retrospectively analyzed. Anatomical structures and variations such as nasopalatine canal(NPC), canalis sinuosus(CS), antral alveolar artery(AAA), were evaluated in multiplanar reformation(MPR) sections which are axial, sagittal and coronal can be viewed in consistence with each other. Results: The incidence of anatomical variation of CS in the right region was similar according to gender. The “Funnel” appearance of the NPC shape was found most common shape in both female and male patients (n = 89; 37.1% for females and n = 71; 27.3% for males). Conclusion: CBCT has become the most popular 3D imaging method in dental practice especially for planning dental implants. Understanding the relationship with important anatomical structures before implant applications is crucial in dealing with potential complications that may arise afterward. Assessing significant anatomical structures by CBCT and taking precautions against possible risks facilitate the work of dentists during and after procedures. © The Author(s), under exclusive licence to Springer-Verlag France SAS, part of Springer Nature 2024.
Keywords: Anatomical variations; CBCT; Dental Implant; Maxillofacial anatomy